Large diameter hemicraniectomy does not improve long-term outcome in malignant infarction - Lehrieder, Dominik; Müller, Hans Peter; Kassubek, Jan; Hecht, Nils; Thomalla, Götz; Michalski, Dominik; Gattringer, Thomas; Wartenberg, Katja E.; Schultze-Amberger, Jörg; Huttner, Hagen; Kuramatsu, Joji; Wunderlich, Silke; et al. (Journal of Neurology, 2023)
Introduction: In malignant cerebral infarction decompressive hemicraniectomy has demonstrated beneficial effects, but the optimum size of hemicraniectomy is still a matter of debate. Some surgeons prefer a large-sized hemicraniectomy with a diameter of more than 14 cm (HC > 14). We investigated whether this approach is associated with reduced mortality and an improved long-term functional outcome compared to a standard hemicraniectomy with a diameter of less than 14 cm (HC ≤ 14). Methods: Patients from the DESTINY (DEcompressive Surgery for the Treatment of malignant INfarction of the middle cerebral arterY) registry who received hemicraniectomy were dichotomized according to the hemicraniectomy diameter (HC ≤ 14 cm vs. HC > 14 cm). The primary outcome was modified Rankin scale (mRS) score ≤ 4 after 12 months. Secondary outcomes were in-hospital mortality, mRS ≤ 3 and mortality after 12 months, and the rate of hemicraniectomy-related complications. The diameter of the hemicraniectomy was examined as an independent predictor of functional outcome in multivariable analyses. Results: Among 130 patients (32.3% female, mean (SD) age 55 (11) years), the mean hemicraniectomy diameter was 13.6 cm. 42 patients (32.3%) had HC > 14. There were no significant differences in the primary outcome and mortality by size of hemicraniectomy. Rate of complications did not differ (HC ≤ 14 27.6% vs. HC > 14 36.6%, p = 0.302). Age and infarct volume but not hemicraniectomy diameter were associated with outcome in multivariable analyses. Conclusion: In this post-hoc analysis, large hemicraniectomy was not associated with an improved outcome or lower mortality in unselected patients with malignant middle cerebral artery infarction. Randomized trials should further examine whether individual patients could benefit from a large-sized hemicraniectomy. Clinical trial registration information: German Clinical Trials Register (URL: https://www.drks.de ; Unique Identifier: DRKS00000624).
CRIS-Team Scopus Importer:2023-05-26
Keywords: Functional outcome; Hemicraniectomy; Malignant stroke; Middle cerebral artery infarction; Size of hemicraniectomy